A simulation study to quantitatively assess the performance of electronic prescribing systems in English NHS Hospital Trusts - Stephanie Klein; Athanasios Tsanas; Jamie Coleman; Rebecca Osselton; Jude Heed; Ann Slee; Neil Watson (Scientific Reports, 2025)
Abstract Prescribing errors are a source of preventable harm in healthcare, which may be mitigated using Electronic Prescribing (EP) systems. Anyone who routinely prescribes medication could benefit from digitally assisted automated checks to identify whether a prescription should potentially not be allowed (e.g. drug allergy). National Health Service (NHS) Trusts have implemented a range of EP systems; however, their performance has not hitherto been evaluated. We developed the web-based Electronic Prescribing Risk and Safety Evaluation (ePRaSE) tool, which comprises a bank of prescribing scenarios to evaluate the performance of EP systems. We solicited ePRaSE testing: 68 pharmacists from across 45 English NHS Trusts, utilising 13 different EP systems volunteered for the study. We found considerable variability in mitigation performance (systems correctly identifying risk of error when prescribing) across both NHS Trusts and EP systems. Moreover, we found that mitigation performance varied considerably across NHS Trusts using the same EP system, strongly suggesting there are opportunities to optimise performance within systems. The ePRaSE tool is effective in identifying variability in risk management between NHS Trusts and EP systems. Wider use of this tool may facilitate improvements in EP system configurations, thus minimising potential harm from prescribing errors.